(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Examination of the platelet aggregation test (PAT) and Maximum Amplitude – Thromboelastography (MA-TEG) ​​are two ways of assessing platelet function. Examination of the platelet aggregation test aims to detect any disturbance of platelet function based on changes in light transmission after adding an agonist. At the same time, the MA parameter of TEG shows the strength of the clot, which is related to platelet count and function, as well as their interaction with fibrin. This study aims to analyze the relationship between the results of the platelet aggregation test and the MA parameter of TEG in assessing platelet function in COVID-19 patients. Method: The type of research used is correlation research with a sampling technique, purposive sampling. Examination of PAT used the Aggregometer Chrono-Log Model 490 while checking MA values ​​used a Thromboelastography 5000. The correlations for the variables studied were analyzed statistically. Results: The results of PAT in COVID-19 patients for each agonist showed different results. Most of the epinephrine and ADP agonists (60%) showed normoaggregation. In comparison, most collagen agonists (66.6%) showed hypoaggregation, while the value of the parameter MA-TEG in COVID-19 patients showed increased results: 75.2 (34.8 – 82.2). The correlation between each PAT agonist and MA-TEG showed no correlation. This conclusion is drawn based on the p-value > 0.05. Each p-value between variables is epinephrine with MA-TEG = 0.689, ADP with MA-TEG = 0.945 and collagen with MA-TEG) = 0.282.Conclusion: There is no significant correlation between PAT and TEG's MA parameter in assessing platelet function in COVID-19 patients.